SPEECH DISORDER FOR THE CHILDREN UNDER THREE YEARS OLD: THE STUDY OF NEUROLINGUISTICS (GANGGUAN WICARA PADA ANAK DI BAWAH TIGA TAHUN: SUATU KAJIAN NEUROLINGUISTIK) - Johan, Mhd.; Radica Suri, Selvi (Jurnal Gramatika, 2019)
Neurolinguistics is the study of how humans acquire language. This study has two objectives, the first objective is to explain which level the phonemes are spoken by respondents the second is to explain the morphemes produced by respondents in speaking. To collect data from this study, researchers used a participatory option personal method, where researchers were actively involved in provoking respondents to talk more. Then the method used is records and techniques noted. Then to analyze this data researchers using the method of distribution / distribution method will be supported by the immediate segmenting constituents technique and basic techniques with the process of adding, dropping and changing, After the data collection and data analysis are considered complete, the results are obtained. The results are the presence of a process of dissolution, change. Immersion that occurs in the research data can occur in all positions, both front, center, and behind the morpheme. Meanwhile, changes also occur in all areas. The most dominant phoneme is obtained in phoneme / r /> / l /. While the phoneme / r / in the antepenultimate position cannot be told by the respondent at all, so there is a breakdown of the phoneme / r /.